A6.22 Specialised pro-resolving lipid mediators in chronic inflammation: a comparison between rheumatoid arthritis and osteoarthritis. (13th February 2015) - Jónasdóttir, HS; Brouwers, H; Kwekkeboom, JC; Huizinga, TW; Kloppenburg, M; Toes, RE; Giera, M; Ioan-Facsinay, A
Abstract : Background and objectives: Inflammation is usually a self-resolving process. The resolution phase involves several cells and molecules that act in a coordinated manner to suppress inflammation, help clearance of apoptotic cells and restore tissue homeostasis. Among these molecules, the pro-resolving specialised lipid mediators (SPM) have emerged as biomarkers and potent mediators of the resolution process. We hypothesised that the underlying cause of chronic inflammation in Rheumatoid Arthritis (RA) and Osteoarthritis (OA)could be the failure of activating pro-resolving mechanisms, involving poly-unsaturated fatty acids (PUFA) and their biologically active metabolites. Methods: To investigate this, we have collected synovial fluid from 20 RA and 33 OA patients. We measured more than 50 analytes in the cell-free supernatant, including SPM, their pathway markers and accompanying PUFA, using liquid chromatography combined with mass spectrometry (LC-MS/MS). To this end, we have set-up a novel analytical platform, characterised by a simplified work-up protocol and high-throughput capabilities, making it particularly suitable for clinical studies. Moreover, we have quantified and characterised the cellular infiltrate using flow cytometry and the appropriate combination of antibodies directed against cell surface markers. Results: By using as little as 40 µL of synovial fluid, we could demonstrate the presence of significant amounts of 5-HETE; 12-HETE; 15-HETE; 10S, 17S-diHDHA; PGE2 ; 17-HDHA, a series of other hydroxylated analytes and a number of PUFA in synovial fluid of both patient groups. Remarkably, analyses of lipid mediator concentrations revealed higher levels of 12-HETE, 17-HDHA and the pro-resolving 10S, 17S-diHDHA in OA versus RA patient samples, indicating a stronger activation of pro-resolving pathways in OA than in RA. Analyses of the cellular infiltrate indicated that in general, less infiltrating cells were found in OA than in RA and the majority of the infiltrating cells were monocytes and neutrophils. The number of monocytes correlated with the number of neutrophils in both diseases, suggesting no specific recruitment of a certain cell-type. Interestingly, we found a strong negative correlation between numbers of infiltrating cells and the concentration of 17-HDHA in the pooled RA and OA samples, as well as the individual disease samples, suggesting a possible biological role for this lipid in cell migration blockage. Conclusion: These data indicate that both inflammatory and pro-resolving pathways are activated in RA and OA synovial fluid. However, the level of inflammation is less in OA than in RA and this could be explained by the presence of higher levels of SPM in OA compared to RA.